Improving the Reading Comprehension of the Eight Grade Students of SMP Negri 3 Parepare by Using Short Story - Citra Dewi; Rafi'ah Nur; Patahuddin (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2019)
Reading skill is one of the important abilities in learning and teaching process. Reading very important for student, because by reading the student can explore their ideas, creativity and knowledge.Besides, most students feel bored with reading. Those become some of the considerations of the researchers to conduct this research when doing an observation SMP Negeri 3 Parepare.Thus, the objective of this research was to find out whether or not the implementation of short stories text can improve the reading comprehension of the eight grade students of SMP Negeri 3 Parepare. Because students to showing the low ability in reading. Then, modifying the instructional methods can become a problem solving for the lack of the students in reading. In this case, the implementation of the short story as an instructional method is suggested to overcome the problem. Then, objective of the research is to find out whether or not the use of short story method can improve the reading comprehension of the eight grade students of SMP Negeri 3 Parepare significantly. The method used in this research was quasi-experimental method that used two classes which consisted of one experimental clas and control class. The experimental class consisted of 20studets and the control class consisted of 20 students. So, the total of the sample was 40 students. The data required from reading comprehension test was analyzed by using SPSS 21. The result of the data analysis shows that the students’ reading comprehension improved. It can be seen from the mean score of pre-test and pos-test between experimental class and control class. The mean score of experimental class in pre-test was 36.50 and in pos-test was 59.50. Meanwhile, the mean score of the control class 34.45 and in pos-test was 45.65. It indicated that the improvement of the experimental class who got treatment by using short stories text was higer than control class who did not get treatmen by using short stories text. After analyzing the data by using the test formula, the result of the t-test value in post-test was 4.009 and t-table value was 2.032. It means that the t-test value (4.009) was higher than t-table value (2.032). This indicates that H1 was accepted and H0 was rejected and the students who were taught through Short Story are better than the students who were taught trough Longer Story.